Arctic Ocean Acidification 2013: An Overview. - Arctic Monitoring and Assessment Programme (AMAP) (Arctic Monitoring and Assessment Programme (AMAP), 2014)
This overview report presents a summary of the first comprehensive assessment of Arctic Ocean acidification (AOA) conducted by the Arctic Monitoring and Assessment Programme (AMAP). More than 60 international experts collaborated to conduct the assessment, the scientific findings of which are documented in the AMAP Assessment 2013: Arctic Ocean Acidification report. Additional experts provided independent review. In compiling this assessment, the AMAP team of experts identified significant gaps in critical data sets and current scientific understanding. On the basis of the assessment, the AMAP Working Group developed the Arctic Ocean Acidification Assessment: Key Findings and Arctic Ocean Acidification Assessment: Summary for Policymakers. The Key Findings and associated recommendations, which were presented to the Arctic Council Ministers at their meeting in Kiruna, Sweden in May 2013, are reproduced in the executive summary that appears on pages ixxi of this report. The response of the ministerial representatives of the Arctic Council is included in the box on page xi. This overview report, Arctic Ocean Acidification 2013: An Overview, is also produced under the responsibility of the AMAP Working Group and is intended to provide a readable summary of the 2013 Arctic Ocean acidification assessment and its findings (summarised on page 26). It includes suggestions for advancing knowledge of Arctic Ocean acidification and its possible implications for the people of the Arctic (on page 25). The fully referenced and peer-reviewed AMAP Assessment 2013: Arctic Ocean Acidification report constitutes the scientific basis for the majority of the information and graphics presented in this overview report. The ocean-acidification assessment complements previous AMAP assessments of Arctic climate change, including the Arctic Climate Impact Assessment and the Snow, Water, Ice and Permafrost in the Arctic (SWIPA) assessment. Where this overview report incorporates information from the SWIPA assessment, this is indicated by ...